CIPP모형을 활용한 IT분야 산학협업 인턴쉽 프로그램에 대한 평가 - 이중만(Jungmann Lee); 양해봉(Haebong Yang); 신준우(Junwoo Shin); 설정선(Jongsun Seol) (한국콘텐츠학회 논문지, 10(1), 2010)
The purpose of this study is to develop New-IT internship and to search for the way to reduce quality mismatch and unemployment ratio and to ultimately enhance its effectiveness of university-industry collaboration(UIC) in the field of information technology in Korea. To achieve the goal of this study, we tried to come up with more job creation than educational UIC. The survey(based on CIPP model) based on the reaction of companies and interns participating in IT internship program promoted by MKE(Ministry of Knowledge and Economy) shows that intern experience helped them to get jobs and longer intern period gave them to find job more easily. This program is designed to focus on intern matching between students' major and their intern jobs, and requires new employees' level of job quality. They(56%) preferred to hire local college students majoring in special technology area related to regional innovation industry cluster. It also found that intern companies(87%) wanted to participate in this program again and hired intern students(61%) as showing the possible connection of internship and employment. IT Internship program affected students(68.3%) good images about small and medium enterprises(SME) after finishing internship. 본 연구는 기업이 원하는 맞춤형 인재육성과 함께 질적 불일치 해소와 최근 대두되고 있는 무업자 증가 및 청년실업률 완화에 기여할 수를 있기 위해 단순 교육차원의 산학협력이 아닌 고용이라는 실질적 가치창출로 연계되는 IT인턴쉽 모델 개발과 활성화를 목적으로 하고 있다. IT인턴쉽 시범운영한 참여기업 및 인턴학생에 대해서 CIPP모형을 활용한 실태조사를 한 결과, 재학 중의 인턴쉽 경험이 취업에 도움을 주고 있음을 알 수 있었으며, 현장실습기간이 길수록 취업에 도움의 정도가 커진다고 생각하고 있다. 학력보다는 전공 및 직무위주의 인턴사원을 매칭하고 사전교육의 효과로 신입사원 수준의 업무를 부여하고 수행하여 인턴쉽 내용이 질적으로 상승하게 되었다. 지방학생 채용비율 56%로 지역특화 산업과 연관된 기술 분야의 지방학생에 대한 기업의 선호도가 있는 것으로 나타났으며, 연수기관의 87%가 재참여 희망하였으며, 이중 61% 연수생을 채용 희망의사를 표시하여 고용연계 가능성을 확인 하였다. 또한 연수생들의 68.3%가 인턴 후 중소기업에 대해 긍정적으로 이미지 전환되어 인턴사업이 중소기업에 대한 기존의 부정적 선입견 완화에 기여 하고 있음을 보여 주고 있다.